Analysis of Fluid-Structure Interaction Effects of Liquid-Filled Container under Drop Testing - Chakrit Suvanjumrat,; Tumrong Puttapitukporn,; Satjarthip Thusneyapan, (Agriculture and Natural Resources, 2008)
An analysis of drop-impact test for plastic containers is a first step toward the simulation of impact events for design and development purposes. Computer methods based on finite element analysis (FEA) were able to predict the performance of liquid-filled plastic containers to withstand drop-impact loading without rupture. This paper presented results of finite element analysis studied drop-test of liquid-filled plastic bottles. The aim of this study was to determine the accuracy of a non-linear explicit FE code in the MSC.Dytran program, by comparing FEA results to experiments. This paper is to lay down the effective procedures for analyzing the drop-test using FEA, which are appropriate for the design and development of plastic containers.